Control release of acyclovir nanocristals from electrospun nanofibers: comparison of two polymeric matrices - Costa, Tiago (2017)
The objective of this study is to develop a novel system for cutaneous application of ACV that is capable of a controlled release of the drug overcoming the limitations of the conventional topical formulations.